Suplementasi Tepung Kunyit (Curcuma domestica) dalam Ransum Terhadap Karakteristik Organoleptik Telur Ayam Ras - Kususiyah; Romadoni, Muhammad Iqbal; Kaharuddin, Desia (BPFP Universitas Bengkulu, 2022)
This study aimed to evaluate the effect of turmeric flour supplementation in the ration on the organoleptic characteristics of purebred chicken eggs. Forty chickens aged 36 weeks were randomly distributed into four treatments, each treatment consisting of 10 tests, with a Complete Randomized Design. Treatment (P0) without turmeric flour supplementation, the other treatment was turmeric flour supplementation successively P1: 0.75%; P2: 1.50% and P3: 2.25%. The variables observed included the color of the yolk, taste, aroma (smell), and texture of the egg that had been boiled. Observation of the organoleptic characteristics of eggs is carried out in the ninth week after the administration of turmeric flour. The data obtained are tabulated and further discussed descriptively. The results showed that turmeric flour supplementation in the ration against the egg yolk color score ranged from 3.35-3.70, taste 3.18-3.34, smell/aroma 3.14-3.20, and texture 3.08-3.17. Based on the results of the study, it can be concluded that turmeric flour supplementation (Curcuma domestica) up to the level of 2.25% in the ration is only able to improve the color characteristics of the yolk from a bit like to like but does not decrease the taste characteristics, aroma/smell and texture of purebred chicken eggs after boiling. Key words: Supplementation, Turmeric Flour, Organoleptic Characteristics ABSTRAK Penelitian ini bertujuan mengevaluasi pengaruh suplementasi tepung kunyit dalam ransum terhadap karakteristik organoleptik telur ayam ras. Ayam umur 36 minggu (46 ekor) didistribusikan secara Acak ke dalam empat perlakuan, masing-masing perlakuan terdiri 10 ulangan, dengan Rancangan Acak Lengkap (RAL). Perlakuan (P0) tanpa suplementasi tepung kunyit, perlakuan lainnya adalah suplementasi tepung kunyit berturut-turut P1: 0,75%; P2 : 1,50% dan P3 : 2,25%. Variabel yang diamati yaitu warna kuning telur, rasa, aroma (bau), dan tekstur telur yang sudah direbus. Pengamatan karakteristik organoleptik telur dilakukan pada minggu ke sembilan setelah pemberian tepung kunyit. Data yang diperoleh ditabulasi, dibahas secara deskriptif. Hasil penelitian menunjukkan bahwa suplementasi tepung kunyit dalam ransum terhadap skor warna kuning telur berkisar 3,35-3,70, rasa 3,18-3,34, bau/aroma 3,14-3,20, dan tekstur 3,08-3,17. Berdasarkan hasil penelitian dapat disimpulkan bahwa suplementasi tepung kunyit (Curcuma domestica) sampai level 2,25% dalam ransum hanya mampu meningkatkan karakteristik warna kuning telur dari agak suka menjadi suka tetapi tidak menurunkan karakteristik rasa, aroma/bau dan tekstur telur ayam ras setelah direbus.